Gas-phase Chemistry in the Interstellar Medium: The Role of Laboratory Astrochemistry - Puzzarini, Cristina (Frontiers in Astronomy and Space Sciences, 2022)
"Who" and how? In this simple question the complexity of the interstellar chemistry is contained. "Who" refers to what molecules are present in the interstellar medium (ISM) and "how" to the mechanisms that led to their formation. While the large number of molecules discovered in the ISM (~250) demonstrates the rich chemistry there occurring, a significant number of unknown species are waiting for an identification and the processes that led to the synthesis of the identified species are still hotly debated or even unknown. Gas-phase laboratory studies in the fields of rotational spectroscopy and quantum chemistry provide an important contribution to answering the question above. An overview on the role played by rotational spectroscopy and quantum chemistry to unravel gas-phase chemistry is presented.